PENEGAKAN HUKUM PIDANA TERHADAP JUDI ONLINE DI POLDA SUMATERA UTARA KAITANNYA DENGAN KEABSAHAN PEMBUKTIAN BUKTI ELEKTRONIK - Taryono Raharja; Madiasa Ablisar; Mahmud Mulyadi; Sunarmi Sunarmi (Law Jurnal, 2023)
ABSTRACTSoccer betting and poker are electronic crimes, but in the process of snaring offenses they often stilluse the provisions of Article 303 paragraph (1) of the Criminal Code, instead of referring to theprovisions of Law No. 11 of 2008 concerning Information and Electronic Transactions. The policyposition of Law no. 11 of 2008 is a special position according to the principle of "lex specialis derogatlex generalis". The gap in Article 63 paragraph (1) of the Criminal Code which still regulates theprovisions of special criminal rules is seen to overlap with the position of Article 27 of the ITE Lawwhich carries a penalty of six years in prison. So it is considered important to discuss the rules ofposition in the online gambling investigation procedure at the North Sumatra Regional Police. Thisresearch will examine and analyze 1) How is criminal law enforcement against online gamblingcrimes at the North Sumatra Regional Police; and 2) The validity of electronic evidence in provingonline gambling crime cases. The results of the research formulate where law enforcement againstonline gambling crimes prioritizes due process of law indicators; and regarding the validity ofelectronic evidence as digital evidence in uncovering criminal cases of online gambling, it must fullymeet the evidentiary requirements, so that it can be used at the investigative level.Keywords: Law enforcement; online gambling; North Sumatra Police